Comparison of Post Inflammatory Pattern between Intracameral Ceftazidime and Cefuroxime Used for the Prevention of Post-operative Endophthalmitis - Sameer Nagi, Muhammad Moin Arooj Amjad (Pakistan Journal of Ophthalmology, 2019)
Purpose: To compare the post operative inflammatory pattern after phacoemulsification in patients receiving intra-cameral injection of ceftazidime and cefuroxime per-operatively for the prevention of post-operative endophthalmitis. Study Design: Quasi experimental study. Place and Duration of Study: Ophthalmology Department Unit-1, Lahore General Hospital, Lahore from November 2016 to March 2018. Material and Methods: Patients undergoing phacoemulsification with intraocular lens implantation were divided into 2 groups by convenient sampling. Group A received Cefuroxime and group B received Ceftazidime both as 1 mg/0.1ml intra-cameral injections at the end of the routine surgery. The patients were examined pre and post operatively on slit lamp and the number of cells in the anterior chamber (A/C) were counted on first day, first week and 6 weeks after surgery. Results: Out of 260 patients there were 130 in each group. On the first post-operative day in group A there were grade 1 cells in A/C in 22 patients, grade 2 in 93 patients, grade 3 in 14 patients and Grade 4 in 1 patient. In group B there were grade 1 cells in A/C in 11 patients, grade 2 in 96 patients, grade 3 in 20 patients and grade 4 in 3 patients. After one week, in group A, cell counts were grade 0 in 27 patients while in group B, cell counts were grade 0 in 23 patients. After 6 weeks no patient in any group showed any activity in the anterior chamber. Conclusion: There is little difference in post operative inflammatory pattern of intracameral ceftazidime antibiotic prophylaxis as compared to intracameral cefuroxime. Key Words: Endophthalmitis, Cataract Surgery, Cefuroxime, Ceftazidime.